The Training Path of Legal Talents in China’s "New Era" - Song , Shiyong (American Journal of Education and Learning, 2022)
The training of legal talents has been popular in colleges and universities in China, but the social employment situation of law graduates is not optimistic. One of the basic reasons is that higher education of professional law in China was confronted with such variety typical problems as relatively large number of law schools, funds shortage, school leaders lacking sustainable awareness. At the same time, it is difficult for college students to have real legal practice opportunities to improve their legal practice ability. The purpose of this paper is how to improve the effectiveness of legal education in the current situation of the increasing popularity of big data and artificial intelligence (AI). In China, the judicial resources represented by AI have been widely used in practice, but the law teaching in colleges and universities has not adapted to this situation in time. By using the method of data analysis, this paper expounds that in addition to building Marxist colleges in colleges and universities to ensure their political awareness, the Chinese government should increase the investment in higher legal education, further maintain the number of legal higher education institutions, and incorporate real-time tracking such as the application of artificial intelligence in judicial practice into the curriculum in time. This is the key to cultivate talents of rule of law in the "new era". At the same time, sound legal psychology should also be the core of “Rule of Law Talents”.